THE EFFECT OF TEMPERATURE ON THE CVC OF A PHOTOELECTRIC CONVERTER - Rajabov, Nurmuhammed (Физико-технологического образование, 2023)
In this paper, a photovoltaic model analysis was carried out to simulate the actual behavior of a photovoltaic module using MatlabSimulink using the parameters of photovoltaic cells consisting of a single diode, series resistance and shunt resistance. The typical characteristics of a 150 W P 36 multicrystalline solar module were used to evaluate the model. The characteristic curves were obtained from the manufacturer's data sheet, which shows an exact match of the model, and this proves that the module is reliable